2022
DOI: 10.1590/acb370408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different gastrointestinal reconstruction techniques on nutrition, anemia, and quality of life in laparoscopic distal gastrectomy for gastric cancer

Abstract: To explore the effect of different gastrointestinal reconstruction techniques on laparoscopic distal gastrectomy of gastric cancer on the nutritional and anemia status, and quality of life (QoL) of patients. Methods: Eligible patients were randomly divided into three groups (n=36/group): Billroth I anastomosis group, Billroth II combined with Braun anastomosis group, and Roux-en-Y anastomosis group. Related indicators were compared and analyzed. Results: The general data were comparable among the three groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Among the two studies reporting anastomosis time 18,20 anastomosis time was lower in the BB group (WMD, −8.65 min; 95% CI, −9.20 to −8.10; p < 0.00001; Figure 2B). Eight studies [14][15][16][17][18][19][20][21] reported intraoperative blood loss and the meta-analysis revealed the value was similar in the two groups (WMD, −13.44 mL; 95% CI, −28.67 to 1.78; p = 0.08; Figure 2C). The number of harvested lymph nodes was reported in seven studies [15][16][17][18][19][20][21] and was similar between the two groups (WMD, 0.50; 95% CI, −1.71 to 2.71; p = 0.66; Figure 2D).…”
Section: Comparison Of Perioperative Outcomes Between Bb and Rymentioning
confidence: 97%
See 4 more Smart Citations
“…Among the two studies reporting anastomosis time 18,20 anastomosis time was lower in the BB group (WMD, −8.65 min; 95% CI, −9.20 to −8.10; p < 0.00001; Figure 2B). Eight studies [14][15][16][17][18][19][20][21] reported intraoperative blood loss and the meta-analysis revealed the value was similar in the two groups (WMD, −13.44 mL; 95% CI, −28.67 to 1.78; p = 0.08; Figure 2C). The number of harvested lymph nodes was reported in seven studies [15][16][17][18][19][20][21] and was similar between the two groups (WMD, 0.50; 95% CI, −1.71 to 2.71; p = 0.66; Figure 2D).…”
Section: Comparison Of Perioperative Outcomes Between Bb and Rymentioning
confidence: 97%
“…Eight studies [14][15][16][17][18][19][20][21] reported intraoperative blood loss and the meta-analysis revealed the value was similar in the two groups (WMD, −13.44 mL; 95% CI, −28.67 to 1.78; p = 0.08; Figure 2C). The number of harvested lymph nodes was reported in seven studies [15][16][17][18][19][20][21] and was similar between the two groups (WMD, 0.50; 95% CI, −1.71 to 2.71; p = 0.66; Figure 2D). No significant difference was observed between the two groups in terms of hospital stay (WMD, −0.02; 95% CI, −0.19 to 0.14; p = 0.77; Figure 2E) and time to first flatus or defecation (WMD, −0.09; 95% CI, −0.27 to 0.09; p = 0.35; Supporting Information: Figure S1A).…”
Section: Comparison Of Perioperative Outcomes Between Bb and Rymentioning
confidence: 97%
See 3 more Smart Citations